RESCUING THE ISCHEMIC PENUMBRA—OUR EXPIRIENCE - Milosavljevic Tamara; Ivkovic Aleksandar (Sanamed, 2013)
Objectives: Over one million strokes per year are occurring in Europe. Brain stroke is one of the most important death and disability causes in Europe and USA. The main role of perfusion is to determine the border of insult core and ischemic penumbra. Penumbra can be saved with thrombolytic therapy but core have irreversible injuries and represent death of brain cells. Aim: to determine the role of CT brain perfusion in cases of acute brain stroke and following thrombolytic therapy. Methods: We examined 64 patients with acute brain stroke who received thrombolytic therapy after that. All patients were examining on 16 MDCTwith 50 ml of iodine contrast agent following the standard procedure for CT perfusion. Patients were 34 male and 30 female with middle age of 64 years. MRI was made after thrombolytic therapy and compare with perfusion results before therapy. Results: Using an artery and a vein as reference three parameters were measured — blood flow (CBF), blood volume (CBV) and mean transit time (MTT), for each patient. Hemorrhagic was find in 9 (14.01%) patients after thrombolytic therapy. 4 (6.25%) other patients develop new stroke of same but mostly other side of brain. 8 (12.50%) more patients finished lethally. From other 42 patientswith thrombolytic therapywe can positively say that in 31 (48.44%) patients penumbrawas rescued. For other 11 (17.19%) stroke was same size like firstly involved core and penumbra but not bigger. Conclusion: CT perfusion plays major role by showing a curable parts of tissue in brain strokes